HUBUNGAN TINGKAT PENGETAHUAN PREMENSTRUAL SYNDROME DENGAN CARA MENGATASI PREMENSTRUAL SYNDROME DI SMP N 26 PURWOREJO - sholichah, nur; Indah Lestari, Ayu (Lembaga Riset Pengabdian Masyarakat dan Publikasi Ilmiah Institut Teknologi Bhakti Putra Bangsa Indonesia, 2024)
Adolescence, one of which is that young women wh start puberty will experience what is called menstruation, where the problem of premenstrual syndrome can affect the condition of young women. For the results of research studies at SMP N 26 Purworejo, the problems that exist, after being examined and analyzed, it turns out that the root of the problem lies in the lack of understanding of female students. about PMS (Premenstrual Syndrome) and how to treat it. For this type of research using a descriptive survey with a cross sectional approach, the total population was 58 respondents with a total sampling technique of 58 respondents during the research period from August to September 2023. The data collection method used a questionnaire and data analysis tests used data analysis, mean, median, mode, SPSS program. For the research results, the level of PMS knowledge among class VII female students at SMP N 26 Purworejo was in the good category, 40 (69%), 13 (22.4%) sufficient, 5 (8.6%) poor, while there were 32 categories for how to handle PMS. 55.2%) were untreated and 26 (44.8%) were treated. It can be concluded that the 58 respondents who were studied using a questionnaire, the data obtained showed that the most knowledge was in the good level of knowledge category, namely (69%) and the category of how to handle PMS was mostly in the untreated category, namely (55.2%) . From the results of this research, the author hopes that female students will be more active in seeking information about PMS so that their knowledge about PMS increases. Keywords: PMS (Premenstrual Syndrome), Causes, Treatment)